Energy efficient on aspect of clock synchronization in a wireless sensor network - Al-Mekhlafi, Zeyad Ghaleb; Mohd Hanapi, Zurina; Othman, Mohamed; Ahmad Zulkarnain, Zuriati; Saleh, Ahmed M. Shamsan (Asian Network for Scientific Information, 2014)
Recent advances in the areas of Micro-electrical Mechanical Systems (MEMS) spurred the interest of researchers in Wireless Sensor Networks (WSNs). These networks are made up of sensor nodes which have the capability to sense, process and transmit gathered data of an environmental phenomenon of interest. Such synchronization is vital for the proper coordination of the power cycles for energy conservation. Here, a large presence of fireflies employ the principle of pulse coupled oscillators for the emission of light flashes for the attraction of mating partners. With respect to WSNs, the nodes are generally unable to afford packet transmission and reception simultaneously, thus preventing complete network synchronization. This study presents a literature overview concerning the energy efficient on aspect of clock synchronization in a wireless sensor network. In addition, the idea of data transmission based on synchronization can be ensured through the optimization of energy usage periodic data capturing in the wireless sensor network. This study serves as a useful source on clock synchronization to assist WSN researchers and novices to gain a better understanding of the energy efficient on aspect of clock synchronization in a wireless sensor network and to promote effective designs and systems that address this problem.